Farm Women and Their Work in Delta, British Columbia, 1900-1939 - Szychter, Gwendolyn Mary (Simon Fraser University, 1992)
This thesis explores and categorizes the economic contribution of farm women in the Fraser Delta during the period 1900-1939. The sources were mainly oral history interviews, as well as personal diaries, local newspapers, and government documents. In the particular social and economic context in which they ran their households and raised their families, the twenty-four women whose lives were explored shared many common characteristics, but an effort was made to convey a sense of these women as individuals as well as members of a larger group....